Embolization with Onyx of an arterial pseudoaneurysm with an arteriovenous fistula complicating a percutaneous nephrolithotomy - Simões Ferreira, Ana Isabel (2018)
Percutaneous nephrolithotomy (PCNL) has proven very effective in the management of renal stones. However, complications are not so rare, and bleeding is one of the most worrisome; it has a reported incidence of 1%-3% and may happen during track dilatation. In addition, arterial pseudoaneurysms and/or arteriovenous fistulas (AVF) may occur. We report the case of a patient with an intrarenal pseudoaneurysm associated with an AVF, after PCNL. Superselective endovascular embolization with Onyx® was successfully performed, achieving exclusion of the pseudoaneurysm and AVF with preservation of the remaining vascularization of the kidney. We review the literature regarding endovascular management of kidney vascular lesions after PCNL. Selective renal embolization is a minimally invasive procedure, highly effective with a low incidence of complications. Currently, it is considered the most appropriate technique in the treatment of arterial iatrogenic complications following percutaneous renal procedures. Onyx® is an effective, easy to handle, and safe alternative embolic agent for these procedures.